Les sans-État et les droits de l’homme - Olay, Csaba (Verbum – Analecta Neolatina, 2008)
The paper investigates Arendt’s criticism of human rights, taking as a point of departure her analysis of totalitarianism. In analyzing the political catastrophe of the 20th century, she describes, among others, the situation of stateless-people, i.e., the refugees of the 1930s and 1940s, who had lost any citizenship. I delineate her theory of total domination and totalitarianism, and I put her considerations on human rights in this context. The paper discusses Arendt’s basic idea that human rights make no sense without an instance that is able and willing to defend those rights.